Influence of Geoelectric Field on Chemical Reactions on Earth - Shevchenko, Igor V. (Доповіді НАН України, 2016)
The existing understanding of chemical thermodynamics presupposes that at the same temperature and other conditions being equal, the rate of a chemical reaction will always and everywhere on Earth be constant. We have found that geoelectric field generated by the Earth’s ionosphere, is capable of exerting a strong influence on the rate of chemical processes. Because of the revolution of the Earth around the Sun and varying intensity of the solar irradiance the geoelectric field is highly dynamic and causes the rate of some chemical reactions on the Earth to vary over wide ranges within a year.